Komparasi Tingkat Risiko Kredit, Risiko Likuiditas, dan Risiko Operasional Bank Syariah di Indonesia pada Masa Sebelum, Selama, dan Setelah Pandemi COVID-19 - Isnaini Rochmah; Rediyanto Putra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to provide evidence of the long-term impact of the COVID-19 pandemic on the level of risk of Islamic banking in Indonesia. This study examines differences in the level of risk of Islamic banking in Indonesia, especially in credit, liquidity, and operational risks before, during, and after the COVID-19 pandemic. To measure these risks, we used the ratios of NPF Net, NPF Gross, FDR, BOPO, and CIR with a one-way ANOVA analysis tool. This study took a research sample of 11 Islamic banks with the time period 2018-2023. The results showed that There is no difference in credit risk, liquidity risk, and operational risk of Islamic banks in Indonesia.